The relationship between thinking and beyond knowledge and intelligence in secondary education - Zahlouq, Maha; Saleh, Weaam (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
Experienced in the field of graduate studies, with experience in the field of graduate studies (72) students of secondary school students were chosen by the random way, and what about them? The results of the research are to verify the validity of the hypotheses. The results are as follows: 1. The existence of a meaningful relationship in the dreams between the thinking of the cognitive and cognitive intelligence 2. There are statistically significant differences between mean temperatures. 3. There are statistically significant differences between mean temperatures. Based on the results of the study researcher in the need for further studies and field studies in thinking beyond the cognitive and link after studying in the United States high school or other educational stages in thinking beyond the cognitive strategies.